2014
DOI: 10.2215/cjn.10481013
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ESRD and Death in Patients with CKD Not Referred to a Nephrologist

Abstract: Background and objectives Rising prevalence of CKD requires active involvement of general practitioners to limit ESRD and mortality risk. However, the outcomes of patients with CKD exclusively managed by general practitioners are ill defined. Results Overall 64% of patients were in stage 3a, and 4.5% of patients were in stages 3b-5. Patients with stages 1 and 2 were younger, were predominantly men, more frequently had diabetes, and had lower prevalence of previous cardiovascular disease than patients with stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 34 publications
(36 reference statements)
2
67
0
2
Order By: Relevance
“…Estimates from the Italian dialysis and transplant registry reported approximately 45,000-49,000 patients on dialysis from 2011 to 2013 [14]. In contrast, data related to the real-life clinical management and outcomes of stage 1 through 5 CKD patients not on dialysis is extremely limited, with few studies conducted in Italy [15,16]. The aim of IRIDE (Italian obseRvatIonal study on management of CKD patiEnts and related costs), a multicenter, prospective, observational study, was to describe the course of the disease and the clinical management of Italian patients with CKD over a 3-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates from the Italian dialysis and transplant registry reported approximately 45,000-49,000 patients on dialysis from 2011 to 2013 [14]. In contrast, data related to the real-life clinical management and outcomes of stage 1 through 5 CKD patients not on dialysis is extremely limited, with few studies conducted in Italy [15,16]. The aim of IRIDE (Italian obseRvatIonal study on management of CKD patiEnts and related costs), a multicenter, prospective, observational study, was to describe the course of the disease and the clinical management of Italian patients with CKD over a 3-year period.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of CKD are severe, including progression to ESRD and premature development of cardiovascular diseases and death (2)(3)(4)(5)(6)(7). Although no randomized trials have been performed, .20 years of accumulating evidence has suggested that early nephrologist care is associated with slower CKD progression and lower rates of adverse outcomes (8)(9)(10)(11)(12)(13)(14)(15)(16). Despite practice guidelines recommending that patients in CKD stages 4-5 should be under nephrologist care (6,17), late nephrologist care is still common (18).…”
Section: Introductionmentioning
confidence: 99%
“…48 Two more recent studies among elderly individuals, one from Italy and the other from Sweden, independently demonstrated association of higher mortality with CKD category 3B but not 3A. 49,50 Taken together, we strongly believe that this analysis provides a powerful argument in favor of the need for an age-sensitive approach to diagnosing CKD based on GFR alone, perhaps using a threshold of < 45 ml/min/1.73m 2 rather than < 60 ml/min/1.73m 2 in those over 65 years of age.…”
Section: What Are the Consequences Of Normal Kidney Aging On The Diagmentioning
confidence: 99%